Sistem Pendukung Keputusan Pemilihan Tempat Wisata di Kota Kupang menggunakan Metode Analytical Hierarchy Process (AHP) (Yayasan Kawanad, 2023)
Kupang City, as the capital of East Nusa Tenggara Province (NTT) in Indonesia, offers a variety of tourism potential that is rich in history, culture, and natural beauty. The selection of tourist destinations in the city of Kupang is essential, given the diversity of choice available. This study aims to develop a decision support system (SPK) using the Analytical Hierarchy Process (AHP) method in the context of selecting tourist destinations in the city of Kupang. The AHP method is applied at the identification stage of criteria, data collection, weighting criteria, and ranking of tourist destinations. This study involved interviews with tourism experts, surveys, and literature studies to determine relevant criteria, such as accessibility, facilities, and tourist attractions. Furthermore, data related to tourist destinations in the city of Kupang is collected through various sources. The AHP method is used to determine the relative weight of each criterion by involving the opinions of respondents or tourism experts. The results of the study produced a web -based application that can be used by tourists to include their personal preferences on different criteria, thus helping visitors in choosing tourist destinations that are in accordance with their needs and desires.